2020
DOI: 10.1038/s41419-020-2317-3
|View full text |Cite
|
Sign up to set email alerts
|

Bruceine D induces lung cancer cell apoptosis and autophagy via the ROS/MAPK signaling pathway in vitro and in vivo

Abstract: Worldwide, lung cancer remains a leading cause of cancer mortality. Bruceine D (BD) has been shown to induce pancreatic cancer cell death via several different mechanisms. In this study, we demonstrated that BD inhibited lung cancer cell proliferation. Apoptosis and autophagy were the most important mechanisms involved in BD-induced lung cancer cell death, and complete autophagic flux was observed in A549 and NCI-H292 cells. In addition, BD significantly improved intracellular reactive oxygen species (ROS) lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 51 publications
3
93
0
Order By: Relevance
“…These findings suggested that autophagy may exert an oncogenic role in lung cancer progression. By contrast, Fan et al ( 35 ) reported that Bruceine D, a quassinoid compound, which can be extracted from the seeds of Brucea javanica , inhibits lung cancer progression by inducing cell apoptosis and autophagy, suggesting a suppressive role of autophagy in lung cancer progression. These findings indicate that autophagy serves an important role in lung cancer progression, therefore autophagy plays a role in H 2 -induced cell apoptosis in lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggested that autophagy may exert an oncogenic role in lung cancer progression. By contrast, Fan et al ( 35 ) reported that Bruceine D, a quassinoid compound, which can be extracted from the seeds of Brucea javanica , inhibits lung cancer progression by inducing cell apoptosis and autophagy, suggesting a suppressive role of autophagy in lung cancer progression. These findings indicate that autophagy serves an important role in lung cancer progression, therefore autophagy plays a role in H 2 -induced cell apoptosis in lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…Various hypotheses have been proposed to explain the apoptosis of macrophages in advanced atherosclerosis, such as deprivation of growth factors or the presence of toxic cytokines (51,52), yet there is no evidence for these hypotheses in vivo. Several studies have pointed out that an increased accumulation of ROS, the product of endoplasmic reticulum stress, activates MAPK, which in turn causes the release of the mitochondrial pro-apoptotic proteins caspase3/7/9, subsequently leading to cell apoptosis (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that dysregulation of cell cycle leading to uncontrolled cell proliferation and apoptosis evasion are hallmarks of all cancer cell types [29,[38][39][40][41]. Indeed, through various cell proliferation assays like Sulforhodamine B assay, MTT assay, and Cell Counting Kit 8 assay, BD has been established to exhibit anti-proliferative properties against pancreatic cancer cells (PANC-1, SW1990, CAPAN-1) [29,37], lung cancer cells [A549, NCI-H292, non-small cell lung cancer (NSCLC) H460] [28,42,43], chronic myeloid leukemia (K562) [44], breast cancer cells (MDA-MB-231) [30], hepatocellular carcinoma cells (Bel7404, HepG2, Hep3B, Huh7, PLC) [45,46], and osteosarcoma cells (MNNG/HOS, U-2OS, MG-63, Saos-2) [47]. In all of the investigated cancer cell lines, there was increased activation of pro-apoptotic proteins like B-cell lymphoma 2 (Bcl-2) associated protein (Bax) and Bak and downregulation of anti-apoptotic proteins like Bcl-2 and myeloid cell leukemia 1 (Mcl-1) [48], all of which are tightly linked to cellular proliferation and apoptotic pathways like phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of Rapamycin (mTOR), c-Jun N-terminal kinase (JNK), mitogen-activated protein kinases (MAPK), and canonical Wnt signaling pathways ( Figure 1) [49][50][51][52].…”
Section: Anti-proliferative and Pro-apoptotic Effects Of Bdmentioning
confidence: 99%
“…NSCLC constitute the majority of lung cancer cases in the world [95][96][97][98][99][100]. The effects of BD on the NSCLC cell lines A549, NCI-H292, and H460 has been investigated by different groups and reported that BD-induced intrinsic cellular apoptosis was mediated through the MAPK/JNK pathway [28,42,43]. Similar to p38-MAPKs, JNKs belong to the MAPK superfamily and regulate important biological processes like cellular proliferation and apoptosis.…”
Section: Effect Of Bd Against Nsclcmentioning
confidence: 99%
See 1 more Smart Citation